[Miscellaneous hymns] [electronic resource]. - McCullagh, J. B. (James Benjamin), 1854-1921 ([Aiyansh Mission, B.C. : s.n., 1921)
Text in Niska dialect of the Tsimshian language. Portrait bears identification: Late Rev. J. B. McCullagh. Attributed to James Benjamin McCullagh--A bibliography of British Columbia / B.J. Lowther (no. 1067). Electronic reproduction. Mode of access: Internet. 44